(untitled) (Research, Society and Development, 2021)
This study brings the importance of constant educational actions to the professionals of the Jockey Club de Pelotas (JCP). The extension project “ClinEq – Group Of Teaching, Research and Extension in Equine Medicine at the Veterinary Faculty of UFPEL in partnership with the JCP carried out professional training in order to offer knowledge and evaluate the professionals perception of good management practices with racehorses. Six meetings were held with an exposition of the main management themes and three questionnaires regarding the coaches perception in relation to the subject addressed. During the training sessions, it was observed that the participating professionals showed great interest in the content and took advantage of all the topics covered, understanding it as a gain in their professional performance and improving their understanding of the content. Achieving, during the training period, put into practice some of the suggestions presented to improve good handling practices with horses at JCP.